The Role of Surges During Periods of Very Shallow Water on Sediment Transport Over Tidal Flats - Zhang, Qian; Gong, Zheng; Zhang, Changkuan; Lacy, Jessica; Jaffe, Bruce; Xu, Beibei; Chen, Xindi (Frontiers in Marine Science, 2021)
Periods of very shallow water (water depth in the order of 10 cm) occur daily on tidal flats because of the propagation of tides over very gently sloping beds, leading to distinct morphodynamical phenomena. To improve the understanding of the characteristics of velocity and SSC surges and their contribution to sediment transport and local bed changes during periods of very shallow water, measurements of near-bed flow and suspended sediment concentration (SSC) were carried out at two cross-shore locations on an intertidal flat along the Jiangsu coast, China. Furthermore, the role of surges in local resuspension and morphological change was explored. Results indicates that flow and SSC surges occurred at both stations during very shallow water periods. On the lower intertidal flat, flood surges were erosive, while weaker surges on the middle intertidal flat were not. Surges on lower intertidal flats resulted in local resuspension and strong turbidity, contributing up to 25% of the onshore-suspended sediment flux during flood tides, even though they last only 10% of the flood duration. When surges travel across the flats, conditions change from erosional to depositional. Velocity surges on the middle intertidal flat were too weak to resuspend bed sediment, and the associated SSC surges were produced by advection.